A Streaming Potential/Current‐Based Microfluidic Direct Current Generator for Self‐Powered Nanosystems. (25th September 2015) - Zhang, Rui; Wang, Sihong; Yeh, Min‐Hsin; Pan, Caofeng; Lin, Long; Yu, Ruomeng; Zhang, Yan; Zheng, Li; Jiao, Zongxia; Wang, Zhong Lin
Abstract : A simple but practical method to convert the hydroenergy of microfluids into continuous electrical output is reported. Based on the principle of streaming potential/current, a microfluidic generator (MFG) is demonstrated using patterned micropillar arrays as a quasi‐porous flow channel. The continuous electrical output makes this MFG particularly suitable as a power source in self‐powered systems. Using the proposed MFG to power a single nanowire‐based pH sensor, a self‐powered fluid sensor system is demonstrated.